Probable earning manipulation and fraud in banking sector. Empirical study from East Africa - Samuel Nyakarimi (Cogent Economics & Finance, 2022)
The aim of the study was to determine extent of earning manipulations and possible fraudulent activities in banking sector. The study involved banks in East Africa where the financial statements of 34 banks in Kenya, 30 banks in Tanzania and 20 banks in Uganda were analysed. The study used Beneish model to classify banks as manipulators and non-manipulators. Later, probit regression model was applied based on the results of Beneish model to reclassify the banks as fraudulent or otherwise. The study revealed that 79.4% of Kenyan, 83.3% of Tanzanian and 70% of Ugandan banks could be non-manipulators. Further analysis showed that 79.4%, 76.7% and 80% of Kenyan, Tanzanian and Ugandan banks, respectively, were possibly not engaged in fraudulent activities. The study concluded that some banks could have been involved in earning management and fraud. The study contributes earning management literature by providing evidence that earning management is rife in banking sectors in less-developed countries though banks have strict regulations. The study further contributes to mechanisms of reclassification of institutions as either fraudulent or otherwise. The study recommends that financial statements prepared must be given professional autonomy. Further, it was recommended that the auditors should emphasise computations of ratios by financial statement prepared in order to give a clear, true and fair view of financial position of organizations. The study findings can be used by the management, regulators and government bodies in less developed and developing countries to develop policies that would seal the loopholes that fraudsters use.
Keywords: 330; earning management; fraud; banking sector; beneish model; probit model